Human capital theory, the foundation of the Beca 18 program - Choque Martínez, Alejandro (2019)
This research objective is to examine how the human capital theory establishes as the main foundation of the «Beca 18» program. Although its formulation includes approaches such as social inclusion and exclusion, equity and human development; the human capital theory stands out as a foundation on which it is supported and organized. By examining the program’s expectations, indicators, funding types, filters arranged in execution, our conclusion is reaffirmed. The determinant influence of this theory in the program’s design makes possible to uncover its economistic bias, whose objective is to promote in the beneficiary group the search for an economic income above the poverty line, but not its multilateral development.